Laboratory-Developed Tests: A Legislative and Regulatory Review. - Genzen, Jonathan R.; Mohlman, Jeffrey S.; Lynch, Jerry L.; Squires, Michael W.; Weiss, Ronald L. (Clinical Chemistry, 2017)
BACKGROUND: Twenty-five years ago, the Food and Drug Administration (FDA) asserted in a draft document that "home brew" tests--now commonly referred to as laboratory-developed tests (LDTs)--are subject to the same regulatory oversight as other in vitro diagnostics (IVDs)4. In 2010, the FDA began work on developing a proposed framework for future LDT oversight. Released in 2014, the draft guidance sparked an intense debate over potential LDT regulation. While the proposed guidance has not been implemented, many questions regarding LDT oversight remain unresolved. CONTENT: This review provides an overview of federal statutes and regulations related to IVDs and clinical laboratory operations, with a focus on those potentially applicable to LDTs and proposed regulatory efforts. Sources reviewed include the Code of Federal Regulations, the Federal Register, congressional hearings, guidance and policy documents, position statements, published literature, and websites. SUMMARY: Federal statutes regarding IVDs were passed without substantive evidence of congressional consideration toward the concept of LDTs. The FDA has clear oversight authority over IVD reagents introduced into interstate commerce. A 16-year delay in publicly asserting FDA authority over LDTs, the pursuit of a draft guidance approach toward oversight, and establishment of regulations under the Clinical Laboratory Improvement Amendments of 1988 (CLIA'88) applicable to LDTs contributed to community uncertainty toward LDT oversight. Future regulatory and/or legislative efforts may be required to resolve this uncertainty.